2021
DOI: 10.1210/clinem/dgab235
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Tri-ponderal Mass Index Growth Trajectories and Incident Diabetes Mellitus in Early Adulthood

Abstract: Purpose Studies have reported the influence of adolescent obesity on development of adult diabetes, but the effect of the growth pattern during this period has rarely been explored. Also, the tri-ponderal mass index (TMI) was thought to be a better estimation of adolescent body fat levels than the body mass index (BMI), so we sought to investigate whether growth trajectories derived by these two indices could predict incident diabetes. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Table 1 describes the characteristics of the included studies including 14 for the association between TMI and body fat in childhood and adolescence ( 10 , 14 , 18 26 , 41 43 ), 20 for TMI and CVRFs in childhood and adolescence ( 13 18 , 21 , 26 34 , 42 45 ), and 4 for the association in adulthood ( 35 37 , 46 ). Twenty-five of the included studies used a cross-sectional design ( 10 , 13 , 15 28 , 30 34 , 41 43 , 45 ), 2 a retrospective design ( 14 , 44 ), 1 a case-control design ( 29 ), and 4 a cohort design ( 35 37 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 describes the characteristics of the included studies including 14 for the association between TMI and body fat in childhood and adolescence ( 10 , 14 , 18 26 , 41 43 ), 20 for TMI and CVRFs in childhood and adolescence ( 13 18 , 21 , 26 34 , 42 45 ), and 4 for the association in adulthood ( 35 37 , 46 ). Twenty-five of the included studies used a cross-sectional design ( 10 , 13 , 15 28 , 30 34 , 41 43 , 45 ), 2 a retrospective design ( 14 , 44 ), 1 a case-control design ( 29 ), and 4 a cohort design ( 35 37 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The AUCs were low for TMI (0.53, 0.56, and 0.54), as well as for other adiposity indicators such as abdominal volume index (0.61, 0.62, and 0.61), BMI (0.59, 0.60, and 0.59), and WC (0.61, 0.61, and 0.61) in childhood to predict adult homeostasis model assessment 2-insulin resistance (HOMA2-IR), HOMA2-β, and high fasting insulin ( 36 ). However, when considering growth trajectory instead of a single measurement in childhood, a persistently high TMI during adolescence had predicted diabetes quite well in adults (AUC value as high as 0.81) ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it could contribute to the evaluation of the predictive capacity of these indicators to identify people with high risk of prediabetes. Although a recent study reported that a specific PI growth trajectory pattern during adolescence might be critical for diabetes prevention efforts ( 49 ), few studies examined the association between PI and prediabetes in adults. Conicity index was considered as a simple anthropometric index of body fat distribution to assess the central obesity with high accuracy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%